Production of clonal seedlings of black pepper cv. Bragantina under doses of controlled-release fertilizer - Alexandre, Rodrigo Sobreira; Dutra Giles, João Antônio; Siqueira, André Lucas; Paraguassú Rodrigues, Joice; Palacio Araujo, Caroline; Mello, Tamyris; Lins Monteiro Rosa, Thuanny; Lopes, José Carlos (Comunicata Scientiae, 2022)
Commercial substrates and their fertilization are essential for the morphophysiological, nutritional, and sanitary quality of seedlings. In this perspective, this study aimed to evaluate the quality of clonal seedlings of the black pepper cultivar Bragantina under doses of controlled-release fertilizers (CLF) in a commercial substrate. The treatments were constituted by five doses of the CLF Osmocote® 19-06-10 Mini Prill (3-4 months) (0, 2, 4, 6, and 8 kg m-3), with four replications of 16 cuttings. The CLF Osmocote®, especially in doses close to 4.16 kg m-3, showed to be promising for the production of clonal seedlings of the black pepper cultivar Bragantina.